Overview of Teachers' Knowledge About Canva's Innovative Learning Media - Triyono Triyono; Ida Dwijayanti; Sumarno Sumarno (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: As we know, Indonesia has problems with education. These problems include facilities, books and the quality of teachers, one of which is creating learning media. Method: This research method uses a descriptive quantitative approach. Researchers created a questionnaire with 5 questions then distributed the questionnaire using Google Form via WhatsApp Group. Results and Dıscussion: The research results showed that there are still teachers who do not know the Canva application and do not know that the learning media produced with Canva is interesting and effective. The lack of maximum development of learning media carried out by teachers is due to one of the reasons for the teacher's lack of ability to utilize media. Conclusion: The results of the research can be concluded that there are still teachers who have not been able to utilize technology in making learning media properly. This can be a reference in developing interesting learning media by creating an In House Training (IHT) for creating learning media for teachers.